2004
DOI: 10.1128/aac.48.10.3794-3800.2004
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Pyrimethamine and Sulfadoxine in Children Treated for Congenital Toxoplasmosis

Abstract: The population pharmacokinetics of pyrimethamine (PYR) and sulfadoxine (SDX) for a group of 32 children with congenital toxoplasmosis was investigated by nonparametric modeling analysis. A one-compartment model was used as the structural model, and individual pharmacokinetic parameters were estimated by Bayesian modeling. PYR (1.25 mg/kg of body weight) and SDX (25 mg/kg) were administered orally every 10 days for 1 year, with adjustment of the dose to body weight every 3 months. Drug concentrations were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
3
2

Year Published

2005
2005
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 41 publications
1
19
3
2
Order By: Relevance
“…An even higher value of 0.68 L/kg was announced by Wenk et al (37). Similarly, the VD ss value of pyrimethamine in the Obach's database is 0.43 L/kg, while others report for VD ss ranging between 2.12 and 3.06 L/kg (38). Our predicted value of 2.67 L/kg falls in this range.…”
Section: Discussionsupporting
confidence: 47%
“…An even higher value of 0.68 L/kg was announced by Wenk et al (37). Similarly, the VD ss value of pyrimethamine in the Obach's database is 0.43 L/kg, while others report for VD ss ranging between 2.12 and 3.06 L/kg (38). Our predicted value of 2.67 L/kg falls in this range.…”
Section: Discussionsupporting
confidence: 47%
“…The pharmacokinetic data for infants' treatment with pyrimethamine/sulfadoxine (Fansidar) studied by Corvaisier et al, 189 did not establish the concentration of the pyrimethamine/sulfadoxine that is most effi cacious in treating children with CT. They studied 32 infants with CT receiving pyrimethamine/sulfadoxine every 10 days for 1 year, and 101 measurements were collected.…”
Section: • If Maternal Serologic Test Results Was Suggestive Of An Acumentioning
confidence: 99%
“…These include mean or median t 1/2abs (0.5 to 0.8 h versus 0.93 h in the present study), t 1/2␤ (5.6 to 10.9 days versus 8.4 days), V/F (4 to 20 liters versus combined V ss /F of 11.5 liters), and CL/F (0.02 to 0.08 liters/h versus combined CL/F SDOX ϩ CL M /F of 0.047 liters/h). Previous studies have shown monoexponential (3,9,14,32) or biexponential (19,21,25,34,35) SDOX kinetics. We suggest that our 42-day sampling period, compared to Յ28 days in many previous studies (5,12,14,21,32), facilitated identification of a second compartment.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment with the best evidence for use as IPTp is sulfadoxine (SDOX) plus pyrimethamine (PYR) (SP) (22,26,31), but its effectiveness appears paradoxical given the component drugs have a relatively short elimination half-life (t 1/2␤ ), specifically 6 to 11 days for SDOX (12,19,21,24,25,32,34,35) and 3 to 5 days for PYR (3,5,9,11,12,14,19,21,25,30,32,34,35,38). SDOX is acetylated by the enzyme N-acetyltransferase 2.…”
Section: 315 Versus 33284 Mg ⅐ H/liter) Nasdox (801 Versus 1590mentioning
confidence: 99%